Wednesday

October 22, 2014

October 22, 2014

Posted by **Mike** on Monday, January 31, 2011 at 6:40pm.

2x^3+2=0

- Math -
**Reiny**, Monday, January 31, 2011 at 7:00pm2x^3+2=0

divide by 2

x^3 +1=0

now you have a sum of cubes

(x+1)(x^2-x+1)=0

x=-1 or x = (1 ± ?-3)/2 or (1 ± i?3)/2

- Math -
**MathMate**, Monday, January 31, 2011 at 7:00pmFactor the given equation into:

2x³+2 =0

=> 2(x²+1)=0

and use one of the identities:

x³+y²=(x+y)(x²-xy+y²)

x³-y²=(x-y)(x²+xy+y²)

to factor the given equation to linear and quadratic factors.

Hence solve the resulting linear and quadratic equations.

**Answer this Question**

**Related Questions**

Algebra - I have been doing sum of cubes and difference of cubes problems and I ...

Algebra I - what does factoring the sum or difference of two cubes mean

Math (factoring) - Can someone check my answer? 5x^3 - 40 =5(x^3-8) =5(x-2)(x^2+...

Algebra - Which special case is represented by x^2-121? A. the difference of two...

math - factor the polynomial completely. 125s to the third power + 1 This is the...

Math - Some students might argue that if you know how to factor a sum of cubes, ...

math - please help me simplify (x^3+8)/(x^4-16). thanks. The denominator is ...

Alg 2 - x^6-y^6 fist look at as a difference of squares: (x^3)2 - (y^3)2 =(x^3...

Algebra - Simplify (2xy^2+3)((2xy^2)^2-(2xy^2)(3)+(3)^2) This reminds me of (U+a...

maths - Let's denote the three numbers by a1, a2, and a3. Consider the third ...